Time for Verification Essays in Memory of Amir Pnueli - Manna, Zohar; Peled, Doron A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume is dedicated to the memory of the 1996 Turing Award winner Amir Pnueli, who passed away in November 2009. The Festschrift contains 15 scientific articles written by leading scientists who were close to Amir Pnueli either as former students, colleagues or friends. The topics covered span the entire breadth of the scientific work of Amir Pnueli, with a focus on the development and the application of formal methods. Also included is the first chapter of the unpublished Volume III of Zohar Manna and Amir Pnueli$1 (Bs work on the verification of reactive systems using temporal logic techniques.s
Modal and Temporal Argumentation Networks -- Knowledge Based Scheduling of Distributed Systems -- Quantitative Simulation Games -- The Localization Reduction and Counterexample-Guided Abstraction Refinement -- A Scalable Segmented Decision Tree Abstract Domain -- Towards Component Based Design of Hybrid Systems: Safety and Stability -- Mildly Context-Sensitive Languages via Buffer Augmented Pregroup Grammars -- Inference Rules for Proving the Equivalence of Recursive Procedures -- Some Thoughts on the Semantics of Biocharts -- Unraveling a Card Trick -- An Automata-Theoretic Approach to Infinite-State Systems -- On the Krohn-Rhodes Cascaded Decomposition Theorem -- Temporal Verification of Reactive Systems: Response -- The Arrow of Time through the Lens of Computing -- What Is in a Step: New Perspectives on a Classical Question.
Keywords: Computer science; Logic design; Computer Science; Programming Techniques; Mathematical Logic and Formal Languages; Computation by Abstract Devices; Logics and Meanings of Programs